Aspects of Political Education in a Democratic Life to Achieve Smart and Good Citizenship Citizens' Skills - Halking, Halking (Law Research Review Quarterly, 2018)
The aspects of political education are one of the substance of the study of Political Education which is explored in educational institutions. These aspects of political education consist of three aspects, namely cognitive, affective, and psychomotor aspects. First, the cognitive aspect of political education is an aspect that contributes to building citizens' political knowledge. The main problems of citizens' political knowledge that need to be built include the problem of democracy and the rights of citizens, people's sovereignty, state institutional systems, relations between central and regional powers, the political system, general elections and so on. Second, the affective aspect of political education is an aspect that contributes to building the character and alignments of citizens. This affective aspect process is a process of introducing and instilling values ​​to shape the character and partisanship of citizens as well as implementing them in daily life both in their capacity as autonomous free individuals and as responsible citizens. Third, the psychomotor aspect of political education that contributes to building citizen skills which includes intellectual and participatory skills. Intellectual skills are critical thinking skills which include the ability to hear, identify and describe problems, analyze, and carry out an evaluation of public issues. While citizen participatory skills include interacting skills, expertise in monitoring public issues, and expertise influencing public policy.